Answer:
D
Step-by-step explanation:
You just need to calculate it as usual. Might as well do in fraction form for clearer understandings
Answer:
tohw9
ufpa
Step-by-step explanation:
jfapn
abjllj shllhphkvq gohahogsv 79qy75j
(2x) + 11 < 44
x is multiplied by two because we are looking for twice of x. 11 is added to the 2x because we are looking for eleven more than the sum of twice of x. Since 2x + 11 is less than 44, we use the lesser than ( < ) symbol.
Answer:
14x^3+39x^2+18x+20
Step-by-step explanation:
Answer:
Simplifying
(4x + -6) = (x + 6y)
Reorder the terms:
(-6 + 4x) = (x + 6y)
Remove parenthesis around (-6 + 4x)
-6 + 4x = (x + 6y)
Remove parenthesis around (x + 6y)
-6 + 4x = x + 6y
Solving
-6 + 4x = x + 6y
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
-6 + 4x + -1x = x + -1x + 6y
Combine like terms: 4x + -1x = 3x
-6 + 3x = x + -1x + 6y
Combine like terms: x + -1x = 0
-6 + 3x = 0 + 6y
-6 + 3x = 6y
Add '6' to each side of the equation.
-6 + 6 + 3x = 6 + 6y
Combine like terms: -6 + 6 = 0
0 + 3x = 6 + 6y
3x = 6 + 6y
Divide each side by '3'.
x = 2 + 2y
Simplifying
x = 2 + 2y